New Automated Industrial Technologies for Improving Chemical Penetration of Bovine Pieces in the Raw Material Processing and Conditioning Areas of Gelatine Manufacture - Wittich, William John (University of Canterbury. Chemical and Process Engineering, 2008)
The production of gelatine at Gelita N.Z. Ltd. is a time consuming process. The time limiting step in the process is the pre-treatment of the collagen tissue of the raw material in a lime/sodium sulfide solution. The liming solution breaks down the collagen in the tissue to gelatine. This is a necessary step prior to the extraction of gelatine from the hide pieces. The current liming process takes nearly 50 days to complete. Methods were investigated to increase the rate of penetration of the chemicals into the bovine hide raw material. An increase in the penetration of the liming solutions would lead to shorter processing times for this step in the process. The methods that were investigated were temperature controlled mixing, fluidization of the hide pieces and the use of ultrasound. Of all the methods tested, the fluidization of the hide pieces gave the best results. The pretreatment time of the hide pieces was reduced 9 days with this technique. Methods were also investigated to monitor the levels of conditioning in the raw material An accurate technique to measure hide conditioning was important to pilot plant trials. This helped determine how well any of the trail methods increased the penetration of chemicals into the hide pieces. The use of an ultraviolet dye proved an effective method of measuring conditioning for all the pilot plant trials. The level of chemical penetration was monitored by assessing the penetration of the UV dye. The penetration of the UV dye could be quantified by using imaging software. A possible method of monitoring conditioning in full-scale production was tested. It was determined that the glycosaminoglycans and soluble collagen released into the liming solution could be accurately measured, and related to the overall conditioning of the raw material.